Sea Ice and Water Mass Influence Dimethylsulfide Concentrations in the Central Arctic Ocean - Uhlig, Christiane; Damm, Ellen; Peeken, Ilka; Krumpen, Thomas; Rabe, Benjamin; Korhonen, Meri; Ludwichowski, Kai-Uwe (Frontiers in Earth Science, 2019)
Dimethylsulfide (DMS) is a biogenic trace gas with importance to aerosol formation. DMS is produced by microbial degradation of dimethylsulfoniopropionate (DMSP), an abundant metabolite in marine microalgae. We analyzed DMS and DMSP concentrations in surface water in the central Arctic Ocean during two expeditions north of 79°N in 2011 and 2015. We identified three regions, which were characterized by different DMS and DMSP concentrations, dependent on the regional water masses and the relative movement of sea ice and water to each other. In addition, correlations between DMS and DMSP and correlation of the two sulfur compounds to autotrophic biomass (as chlorophyll a) differed in the regions. In the area of the nutrient rich Atlantic water inflow and short contact of this water with sea ice, DMS is present in high concentrations and correlates to DMSP as well as chlorophyll a. At two stations, particularly high DMS concentrations were found in conjunction with under-ice phytoplankton biomass peaks. In contrast, in mixed Atlantic and Pacific water with strong polar influence, where long-term contact between sea ice and water causes persistent stratification, only little DMS is found. Further, the correlations to DMSP and chlorophyll a are lost and the ratio of DMS to DMSP is about one order of magnitude lower, pointing towards consumption of DMSP without the production of DMS. We conclude that the duration of sea ice influence and source of the surface water do not only lead to differences in phytoplankton productivity, resulting in different DMSP concentrations, but also influence microbial recycling of DMSP to DMS or other compounds. DMS production, as possible source for aerosols, is thus presumably lower in the strongly sea ice influenced central Arctic areas than what could be expected from DMSP concentration or biomass.